Transcatheter Aortic Valve Implantation in Younger Patients: A New Challenge - Giacomo Virgili; Salvatore Mario Romano; Renato Valenti; Angela Migliorini; Pierluigi Stefàno; Niccolò Marchionni; Nazario Carrabba (Medicina, 2021)
The number of aortic stenosis patients in Western countries is increasing, along with better life conditions and expectancies. Presently, the volume of percutaneous transcatheter aortic valve implantations (TAVIs) is incessantly increasing, and has already overcome the surgical replacement procedure volume. According to the literature, TAVI is a feasible procedure even among low surgical risk patients, and American guidelines have extended the indications for TAVI, including shifting patient evaluations from high/low STS scores to old/young patients, a “paradigm shift” of aortic stenosis evaluation. As a result, low-risk young (<75 years-old) population management could be the next challenge in cardiology. To manage the life conditions of a 65 year old patient affected by aortic stenosis who is undergoing TAVI, one of the most crucial issue will be bioprosthesis durability and the appropriate intervention to make in cases of valve dysfunction or failure.